2021
DOI: 10.3390/genes12081253
|View full text |Cite
|
Sign up to set email alerts
|

Screening Potential Reference Genes in Tuta absoluta with Real-Time Quantitative PCR Analysis under Different Experimental Conditions

Abstract: Tuta absoluta is one of the most significant invasive pests affecting tomato plants worldwide. RT-qPCR has emerged as one of the most sensitive and accurate methods for detecting gene expression data. The screening of stable internal reference genes is the most critical step for studying the molecular mechanisms of environmental adaptability. The stable reference genes expressed in T. absoluta under specific experimental conditions have not yet been clarified. In this study, seven candidate reference genes (RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…We found that no standard reference gene is suitable for RT–qPCR analysis. Reference genes, such as actin, tubulin, tef1, NADP, and ubiquitin, are widely used in different species 18 , 20 , 22 24 . However, appropriate reference genes are not uniform across diverse species, and even in different treatments or tissues of the same species 18 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that no standard reference gene is suitable for RT–qPCR analysis. Reference genes, such as actin, tubulin, tef1, NADP, and ubiquitin, are widely used in different species 18 , 20 , 22 24 . However, appropriate reference genes are not uniform across diverse species, and even in different treatments or tissues of the same species 18 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Actin, GAPDH, tubulin, and ubiquitin are used commonly in analysing gene expression levels in plants 23 26 . However, there are no standards to use as reference genes in various species or tissues 24 . The best reference genes were generally confirmed by analytical tools, such as GeNorm, NormFinder, and BestKeeper 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the identified CYP genes was performed using RT-qPCR (Real-Time Quantitative Reverse Transcription PCR) with their gene-specific primers (Supplementary table 2) with the internal reference gene, RPS-13 (Yang et al ., 2021). The cDNA from G1 and G20 population was prepared and diluted at 10 ng μl −1 before setting the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, the online tool RefFinder (https://www.heartcure.com.au/reffinder/, accessed on 8 October 2023) was employed to determine the weighted geometric means in the form of stability values derived from the aforementioned algorithms. This allowed for the establishment of a consensus ranking regarding the stability of the reference genes [29][30][31]. Moreover, the GeNorm algorithm was used to determine the most suitable quantity of reference genes by evaluating pairwise variance values (V).…”
Section: Determination Of Reference Gene Expression Stabilitymentioning
confidence: 99%